Impact of liquidity on Malaysian public listed companies performance / Hellenda Valentine - Valentine, Hellenda (2014)
Purpose of this study was to determine the relationship between liquidity and performance of Malaysian public listed companies measured by profitability and impact of liquidity to companies' performance during global financial crisis. Liquidity is crucial thing for daily operation especially on short term obligations. The population of this study was all industrial product and trade and services sector companies listed in Bursa Malaysia from 2007 until 2011 and sampling method based on Krejcie & Morgan (1970). Besides that, data are collected based on secondary sources. In order to test the hypotheses, regression analysis was used to analyze impact of liquidity on profitability. Meanwhile, Pearson correlation analysis used to find out the relationship between liquidity and profitability. This study reveal that all independent variable, CR and QR have no significant relationship with dependent variable, ROA. However,during global financial crisis from 2007 until 2008, CR have significant relationship with ROA which also means that liquidity is important factor that companies need to consider especially during unexpected event such as global financial crisis.